The values of parks to the house residents / Farahwaheeda Shukur, Noriah Othman and Abdul Hadi Nawawi. - Shukur, Farahwaheeda; Othman, Noriah; Nawawi, Abdul Hadi (Universiti Teknologi MARA Cawangan Selangor, 2016)
The presence of a park in a residential area plays an important role for residents living near the park. The focus of this paper is to examine the significance of a park to the house residents. The methods used in this study include interviews with the developer and a survey administered to the residents living near the park. The main findings gathered from the survey reveal that five most important ‘park related factors’ to house residents are (i) good park elements, (ii) conceptual or design of the park, (iii) nearness to the park, (iv) existence of a view to the park, and (v) active area of the park facing the house. Other results also indicate that shade trees, lighting and butterflies are elements preferred to be presence in a park. This research provides knowledge on the preferences of house residents and the importance of parks in a neighbor hood. The information from this research is hoped to be useful to policy makers, local authorities, urban planners, developers, corporate bodies, individuals and other related agencies involved in park and residential property development.